Saint Augustine of Hippo: an intellectual biography - Hollingworth, Miles ([Verlag nicht ermittelbar], 2013)
Out of Africa -- Augustine's intellectual milieu -- Augustine's remarks on his parents -- Reflections on infancy -- Traumas of initiation into the Earthly City -- Cicero and a sense of purpose -- Manichaeism -- On the singular deportment of death, love and grief -- Christian conversion and reflections on the supernatural -- To write against self-consciousness and its effects -- Last days and reflections on the style of man -- Abbreviations of Augustine's writings